2018
DOI: 10.1093/schbul/sby133
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis Reveals the Latent Structure of Negative Symptoms in Schizophrenia

Abstract: Prior studies using exploratory factor analysis provide evidence that negative symptoms are best conceptualized as 2 dimensions reflecting diminished motivation and expression. However, the 2-dimensional model has yet to be evaluated using more complex mathematical techniques capable of testing structure. In the current study, network analysis was applied to evaluate the latent structure of negative symptoms using a community-detection algorithm. Two studies were conducted that included outpatients with schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 47 publications
5
47
0
Order By: Relevance
“…Although the items in Anhedonia, Avolition, and Asociality subscales loaded to the same factor in a previous factor analysis in BNSS 9,18,24,26,27 and CAINS, 13 recent studies revealed that five or more factor models fit better than two-factor models in BNSS and CAINS. 28,[33][34][35] This is in line with the following idea in the original NIMH report: "The five domains may have separate neurobiological substrates and may represent separate therapeutic targets." 5 Some of the neurobiological tasks exploring the biological basis specific to the each of the five domains have been adopted in clinical studies.…”
Section: Discussionsupporting
confidence: 74%
“…Although the items in Anhedonia, Avolition, and Asociality subscales loaded to the same factor in a previous factor analysis in BNSS 9,18,24,26,27 and CAINS, 13 recent studies revealed that five or more factor models fit better than two-factor models in BNSS and CAINS. 28,[33][34][35] This is in line with the following idea in the original NIMH report: "The five domains may have separate neurobiological substrates and may represent separate therapeutic targets." 5 Some of the neurobiological tasks exploring the biological basis specific to the each of the five domains have been adopted in clinical studies.…”
Section: Discussionsupporting
confidence: 74%
“…[65][66][67] A recent categorial formulation distinguished a distress subtype, distinct from the deficit (enduring negative symptom) subtype in chronic schizophrenia patients, 81 and a network analysis of negative symptoms found an inverse relationship with NA. 82 Using continuous measures, others have found higher negative symptoms associated with reduced NA 29,83 and less reactivity to negative stimuli, 84,85 raising the intriguing possibility that affective flattening and amotivation might be an adaptation to NA. On the other hand, studies of anhedonia have suggested that NA might contribute to anhedonia by reducing pleasure seeking behavior, 86 which could reflect a form of secondary negative symptoms, and that ratings of anhedonia, specifically anticipatory pleasure, is reduced by NA.…”
Section: Negative Affect and Schizophrenia Symptomsmentioning
confidence: 99%
“…38,43 Negative symptoms do not reflect a singular construct, 49 but rather two broad dimensions reflecting diminished expressivity and diminished motivation and pleasure, or five discrete domains reflecting anhedonia, avolition, asociality, alogia and blunted affect. [50][51][52] Therefore, exploratory analyses examined associations between trait affect and the two broad negative symptom dimensions, as well as the five domains.…”
Section: The Current Studymentioning
confidence: 99%